The Economic Impact of COVID-19 Outbreak on the Agriculture Sector - Dwia Aries Tina Pulubuhu; Andi Alimuddin Unde; Suwandi Sumartias; Sudarmo Sudarmo; Seniwati Seniwati (Hasanuddin University, 2020)
The COVID-19 pandemic in Indonesia began to be confirmed in early February 2020, it affects many various economic sectors, including agriculture. The COVID-19 created challenges for socio-economic issues. This short note focuses on the impact of COVID-19 outbreak on the agricultural sector. The COVID-19 outbreak had a wide-ranging impact, so that agricultural commodities continued to decline. The government's call to not leave the house resulted in many farmers not doing their activities so that it has an impact on declining farmers' income. The field officers also could not optimally carry out their work as a result the development of farming was not optimal. Various efforts have been made by the government to support the agricultural sector such as building e-marketing and training in processing yields for farmers.